Secrets of power negotiating - Dawson, Roger (Henry Stewart Talks, 2011)
Never say yes to the first offer, Ask for more than you expect to get, Flinch when the other side asks you for a concession, Bracketing your objective, Play reluctant buyer, Look out for the reluctant seller, Using the vise gambit, Never offer to split the difference, Always ask for a trade off concession, The number one pressure point in a negotiation, Give yourself walk-away power by giving yourself options, How to position for easy acceptance, The power negotiators creed